Les garanties du contribuable dans le cadre du contrôle fiscal en droit marocain - Haloui, Khalil (Université de Grenoble, 2011)
La thèse a pour objet d'examiner la question cruciale des garanties légales du contribuable face aux prérogatives importantes de contrôle fiscal dévolues à l'administration à la suite de la mise en place du nouveau régime d'imposition déclaratif au Maroc. Elle se propose alors de rendre compte de l'état du droit positif sur cette problématique et de répondre à la question de savoir dans quelle mesure les nouvelles procédures de contrôle fiscal instituées permettent-elles de protéger les droits du contribuable vérifié. The thesis aims at examining, following the introduction of new tax declaration regime in Morocco, the paramount issue in respect the taxpayer legal safeguards against the tax authorities prerogatives during tax audit . This work intends to report on the applicable law on this issue and to answer the question on how the newly established tax audit procedures may protect the audited taxpayer's rights.
Keywords: Audit powers; Contentieux d'établissement; Contentieux fiscal; Contrôle fiscal; Court appeals; Droit fiscal; Garanties du contribuable; Imposition; Maroc; Pouvoirs de contrôle; Prior administrative appeals; Recours administratif préalable; Recours administratifs; Recours juridictionnels; Tax audit; Tax settlement litigation; Taxpayer’s guarantees

O mercado de títulos públicos: desmaterialização e circulação - Catapani, Marcio Ferro (Universidade de São Paulo, 2011)
O Estado, para obter recursos com o objetivo de financiar suas atividades, recorre ao mercado por meio de dois mecanismos: a obtenção de empréstimos individualizados e o lançamento de títulos públicos. Na realidade atual, a dívida mobiliária alcança volume muito superior ao da contratual, tendo em vista algumas vantagens do mecanismo dos títulos públicos. Entre essas vantagens, pode-se citar um universo maior de potenciais compradores, a possibilidade de execução de política monetária, a maior facilidade de controle, o menor custo de negociação e escrituração. Fenômeno também observado nas últimas décadas, em escala mundial, é de que os títulos públicos sejam emitidos de modo escritural e eletrônico. Nesse contexto, não pode ser aplicado a esses valores o ferramental teórico e normativo dos títulos de crédito. Com efeito, se a doutrina tradicional considerava os papéis emitidos pelo Estado como uma espécie desses títulos, tal constatação não mais se sustenta, em especial diante da completa inexistência de um suporte documental dos ativos eletrônicos. As características e institutos próprios dos títulos de crédito, como a cartularidade, a literalidade, o endosso e o aval não são compatíveis com a realidade negocial que hoje conforma os títulos públicos. Um conceito jurídico que pode explicar a natureza atual dos títulos públicos e permitir o regramento das operações que os envolvem é o de instrumento financeiro. Desenvolvido no âmbito do ordenamento comunitário europeu, esse conceito não se encontra perfeitamente delimitado no ordenamento jurídico brasileiro, mas nada impede a sua construção em sede doutrinária. Tomando por base a noção de instrumento financeiro, o foco da normatização deixa de ser cada título considerado em si, para recair sobre o mercado em que eles são negociados. Assim, ganha relevo o estudo da estrutura institucional desses mercados, bem como das principais operações que neles são travadas. Tais operações incluem a emissão e a oferta inicial, a negociação secundária, o resgate, a rolagem da dívida, bem como eventuais renegociações e alterações unilaterais nas características dos títulos. Para o desenvolvimento de mercados líquidos e eficientes, algumas condições são imprescindíveis, como, por exemplo, a existência de graus mínimos de estabilidade, previsibilidade e segurança, de uma imagem sólida e confiabilidade das instituições participantes, em especial dos entes estatais emissores etc. Além disso, todo o arcabouço normativo deve ser construído levando-se em consideração os interesses de cada grupo de agentes econômicos envolvidos, como forma de tornar atrativa para estes a alocação de recursos na aquisição de títulos públicos. When the State needs to obtain resources in order to finance its activities, it resorts to the market through two main mechanisms: individual loans or public securities. Nowadays, the debt securities total amount is much higher compared to the debts founded on individual loans, due to some advantages of the technology of public securities. Among such advantages, it can be mentioned a larger universe of potential buyers, the possibility of implementing monetary policy, the easier control, and the lower costs of trading and bookkeeping. In recent decades, it has also been noticed that the public bonds are worldwidely issued in both book-entry and electronic ways. In this context, the theoretical and normative tools regarding negotiable instruments can not be applied to these bonds anymore. Indeed, if the traditional doctrine used to consider the public bonds as negotiable instruments, such understanding can no longer take place, specially taking into account the complete absence of any supporting documentation of electronic assets. The peculiar characteristics and rules related to the negotiable instruments, such as the need of the document to enforce the rights, the respect to the terms of the document, the endorsement, and the guaranty are no longer compatible with the present reality of public bonds. A legal concept that can explain the current nature of the public securities and allows the regulation of operations envolving them is the financial instrument. Developed under the European Community law, this concept is not well defined in the Brazilian legal system yet, but nothing prevents its development in our doctrine. Based on the concept of financial instruments, the focus of regulation is no longer each title considered itself, but the markets in which the financial instruments are traded. Thus it becomes important to study the institutional structure of such markets, as well as the leading operations that are performed in the markets scope. Such operations include the issuance and the initial offering, the secondary trading, the redemption, the debt rollover, the renegotiations of the bonds, and the unilateral changes of their characteristcs. In order to develop efficient and liquid markets, certain conditions are essential, such as the existence of minimal degrees of stability, predictability and security; a solid image and reliability of the participating institutions, in particular of the public issuing bodies etc. Moreover, any regulatory framework should be built taking into consideration the interests of each economic agents groups involved, in order to make the allocation of resources in government securities attractive for them.
Keywords: Dematerialization; Dématérialisation; Government bonds; Market; Mercado de capitais; Negotiable instruments; Titres publics; Título de crédito; Títulos públicos

Le traitement du contentieux bancaire - Nemadeu Djuitchoko, Eric Bertrand (Université de Saint-Etienne, 2011)
Notre travail, qui s’inscrit en droite ligne des recherches du CERCRID sur les marc consistait a étudier cette question, dans un secteur particulier. Il s’est agi d’aller au-delà du discours général sur les modes alternatifs de règlement des conflits, pour voir précisément ce qu’il en est en matière bancaire. La recherche du GIP droit et justice confiée au CERCRID, et portant sur la baisse générale du contentieux de l’impayé depuis le début des années 1990, a constitué un élément supplémentaire de notre champ d’investigation. A la conjonction de ces deux préoccupations principales, s’est greffée une grave crise économique mondiale née du crédit hypothécaire aux États-Unis d’Amérique. Tous ces facteurs nous ont conduit a nous intéresser à la prévention et au règlement du contentieux bancaire. Le travail a donc consiste en une large recherche sur le contentieux bancaire, le mot traitement ayant été choisi pour englober a la fois la prévention et le règlement. On comprend ainsi que le sens contextuel du mot traitement va au-delà de l’acception habituelle de ce terme. Trois principaux constats se dégagent de l’étude du contentieux bancaire : il s’agit d’une matière éminemment marquée du sceau de la prévention, d’une matière limitativement marquée du sceau de la médiation et de l’adjudication, d’une matière rarement marquée du sceau de l’arbitrage. La prévention du contentieux bancaire repose sur deux axes majeurs : la réduction des occasions de contentieux, ainsi que la limitation des espaces de discussion. La négociation précontentieuse apparait comme le mécanisme prééminent permettant d’éviter le litige et de régler les différends. En cas de litige, les parties peuvent saisir le médiateur bancaire. Il est également possible de recourir au juge. En cette matière, c’est essentiellement le juge étatique que les parties saisissent. Il va sans dire que l’arbitrage est rare, notamment du fait de l’absence d’imperium de l’arbitre. Our work was done in the framework of CERCRID research on ADR (alternative dispute resolution). the goal was to study this question in a specific sector. we had to go beyond general knowledges on ADR, in order to discover precisely what it was about in the bank sector. the research of the Center « droit et justice », on the falling of the unpaid litigation since the beginning of 1990, which was assigned to the CERCRID, constituted an additional element for our investigations. furthermore, we had to take the sup-primes crises in the USA into consideration. all these factors lead us to work on the prevention and the settling of banking conflicts. the job therefore consisted to do a large research on banking litigation. the word treatment was chosen to include both the prevention and the settling. this is to say that the sense of the word treatment hier goes beyond the common meaning of this word. three main conclusions can be made about the research on banking litigation : it is a matter in which the prevention of conflicts plays a very important role. the mediation and the settling by the judicial court are less important hier. the arbitration is rare.the prevention of conflicts lies on two majors axis : the reduction of conflicts occasions, and the limitation of space for discussions. the negotiation appears to be the most important mechanism to settle disagreements, the banks trying to avoid judicial proceedings. in case of failure, the conflict can be solved by mediation, or by the court. the judicial court is usually the one chosen by the parties at this stage.
Keywords: Banks; Banques; Cautionnement; Contentieux; Crise économique (2008); Investissements; Investments; Litigation; Overindebtedness; Surendettement

Le contrôle au sein des OPCVM : étude comparative entre le droit français et marocain - Madmoun, Fatiha (Université de Strasbourg 3, 2011)
L'impressionnante évolution de l'industrie de la gestion au cours de ces quinze dernières années, notamment par l'utilisation des techniques de gestion ct de financements novatrices ainsi que le recours à des produits structurés de plus en plus complexes, a conduit l'industrie des d'OPCVM à vivre de profondes mutations. En effet, le caractère puhlic de l'épargne collective et le rôle stratégique que jouent les OPCVM en matière de sa canalisation vers le secteur productif, ont conduit le législateur à confier le contrôle de ces organismes à divers organes. L'efficacité, la productivité et la transparence sont de nos jours les maîtres mots dans les milieux financiers. Tous les opérateurs se trouvent dans l'obligation de mettre en œuvre des règles plus pertinentes et plus rigoureuses pour gagner cette bataille. L'étude du contrôle des OPCVM, revient à occulter l'un des principes essentiels des marchés financiers : la nécessité de sécurité et de confiance. En effet, les investisseurs ne s'engageront dans des placements financiers, que si les produits proposés offrent des garanties suffisantes. Cette confiance peut être établie par le contrôle exercé sur ces derniers, ce contrôle est réglementaire ou légale, il s'agit du commissaire aux comptes, en tant qu'organe classique des sociétés, le contrôle interne comme atout des OPCVM, le dépositaire comme organe original de ces derniers et enfin l'organe clef de la protection des marchés financiers qui est l'autorité de tutelle. The impressive evolution of industry management over these past fifteen years, including by the use of the techniques for managing and funding innovative and the use of more structured products increasingly complex, has led the industry and of UClTS to live profound changes. Indeed, the public nature of the collective savings and the strategic role of UCITS in the pipe to the productive sector, led the legislature to entrust the control of these agencies in various organs. Efficiency, productivity and transparency are the watchwords of our days in the financial community. All operators are obliged to implement the more relevant and more stringent rules to win this battle. The study of the control of the UCITS, returned to obscure one of the fundamental principles of the financial markets : the need for security and confidence. Indeed, investors commit in financial investments, that if the proposed products offer sufficient guarantees. This trust can be established by the control exercised over thcse last, this control is regulatory or legal, is the Commissioner of accounts, just as classical organ of the companies, the internal control as UCITS asset, the depositary as original body of the latter and finally the body key to the protection of the financial markets is the supervisory authority.
Keywords: Autorité de tutelle; Autorité des marchés financiers; Commissaires aux comptes; Conseil Déontologique des Valeurs Mobilières (CDVM); Dépositaire; Etude comparative; Marché financier; Maroc; Sociétés d'investissement; Valeurs mobilières; Vérification interne

Vergi Hukukunda birleşme, bölünme ve hisse değişimi işlemleri - Göktuna, Hamdi Deniz Ege (Marmara Üniversitesi, 2011)
Kurumların birleşme, bölünme, kısmi bölünme ve hisse değişimi yoluyla yeniden yapılandırılma işlemleri başta ticaret hukuku olmak üzere, rekabet hukuku, sermaye piyasası hukuku ve vergi hukuku gibi birçok hukuk dalını ilgilendiren çok disiplinli bir alandır. Ticaret hukuku, genel olarak yeniden yapılandırma işlemlerinde şirket alacaklarının ve ortaklarının haklarının korunmasını amaçlamaktayken, vergi hukuku söz konusu işlemler sonucunda ortaya çıkan kâr ile ilgilenmektedir. Yeniden yapılanma işlemlerin vergisel maliyeti, bunların önündeki en önemli engeli teşkil etmektedir. Bu sebeple, tüm hukuk sistemlerinde vergisel açıdan tarafsızlığı sağlayıcı hükümler yer almaktadır.Çalışmamızda, özellikle, üye devletler arasındaki ekonomik ilişkilerin artırılarak, ekonomik gelişmenin ve refahın sağlanması yoluyla güçlü bir topluluk yaratma amacı taşıyan Avrupa Birliği Hukuku ve Türk Hukukunda yeniden yapılandırma işlemlerinin vergisel boyutu incelenmiştir. Avrupa Birliği Mevzuatına uyum sağlama çalışmaları çerçevesinde dolaysız vergiler alanında yapılması gereken düzenlemelerden birisi de vergi kanunlarında şirketlerin bölünmesini ve hisse değişimini kolaylaştırıcı, kalıcı mahiyette hükümler getirmek olmuştur. Dolayısıyla Avrupa Birliği Birleşme mevzuatı, tam üyelik sürecindeki ülkemiz açısından önem arz etmektedir.Çalışmamızın birinci bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerinin kavramsal esasları, Kurumlar Vergisi Kanunu, Türk Ticaret Kanunu ve Yeni Türk Ticaret Kanunu ile ilgili Avrupa Birliği mevzuatı çerçevesinde ortaya konulmaya çalışılacaktır. İkinci bölümde, birleşme, bölünme, kısmi bölünme, aktif transferi ve hisse değişimine ilişkin temel Avrupa Birliği düzenlemesi olan Birleşme Direktifi, Avrupa Birliği Adalet Divanı kararları çerçevesinde incelenecektir. Son bölümde ise Türk vergi mevzuatındaki, birleşme, bölünme ve hisse değişimine ilişkin hükümler tereddütlü noktalara da değinilmek suretiyle ele alınacaktır. Sonuç bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerine ilişkin değerlendirmelerimize yer verilmiştir. Transactions concerning the restructuring of companies through mergers, divisions, partial divisions and exchanges of shares relate to a multi disciplinary domain, including commercial law, competition law, capital markets law and tax law. While commercial law generally aims at the protection of rights of company's creditors and shareholders, tax law is mostly interested with the profit generated through these transactions. The tax cost of restructuring transactions, constitutes the main obstacle for those. For this reason, all legal systems include provisions providing tax neutrality regarding these transactions.In this study, we have analysed the tax law dimension of restructuring transactions especially in Turkish Law and Law of European Union which aims at the creation of a strong community through the development of economic relations between member states. Within the context of harmonisation to the European Union Legislation, one of the necessary regulations concerning direct taxes has been the enactment of tax law provisions enabling the division of companies and exchanges of shares thereof. Consequently, EU Merger Legislation is of utmost importance for Turkey as a candidate state.The first chapter of this study presents the conceptual basis of the transactions in question within the context of Corporate Tax Law, Commercial Law and the New Commercial Law and EU Legislation. The second chapter examines the Merger Directive within the framework of jurisprudences of European Court of Justice. The last chapter deals with problematic issues in Turkish Tax and Commercial laws. We conclude by presenting our evaluations based on previous chapters.
Tez N° 291505
Keywords: Avrupa Birliği hukuku; Avrupa Topluluğu hukuku; Birleşmeler; Change; Corporate Tax Law; Değişim; Division of company; European Community law; European Union law; Hisse senedi devri; Hisse senetleri; Kurumlar Vergisi Kanunu; Mergers; Stock transfer; Stocks; Tax harmonisation; Tax law; Vergi hukuku; Vergi uyumlaştırması; Şirket birleşmeleri; Şirket bölünmesi

Reformulating corporate residence: a coherent response to international tax avoidance - Loomer, Geoffrey (University of Oxford, 2011)
This thesis analyzes the concept of corporate residence, with particular reference to the law in the UK and Canada. It explores why corporate residence is relevant in tax policy, how corporate residence is understood in law, and how revenue authorities respond to the use and alleged 'abuse' of residence rules. Part I argues that the residence of taxpayers generally (individual or corporate) remains a relevant factor in international tax design, that taxation of corporations on the basis of residence has some justification, but that there is a disjunction between meaningful residence-based taxation and current definitions of corporate residence in domestic law and tax treaties. The formulations of residence based on incorporation, central management and control, and place of effective management, particularly as applied to multinational enterprises, are considered and are found to be deficient. Part II critically analyzes the major policy responses of the UK and Canadian governments to the exploitation of corporate residence. It argues that key legislative and administrative responses to international tax avoidance activities, for both outbound and inbound investment, are purportedly based on the acceptance of formal corporate residence yet undermine that concept in an effort to impose tax or refuse treaty relief based on where economic interests actually exist. The responses considered are the application of controlled foreign companies legislation to offshore subsidiaries, the invocation of treaty anti-abuse rules with respect to offshore intermediaries, and the use of overarching general anti-avoidance measures to challenge varied structures that rely on offshore entities. These haphazard anti-avoidance rules are overlaid with revenue authorities' indignation at the motivations that underlie many corporate relocations. It is argued that a more coherent approach would be to focus on the objective reality or unreality of corporate establishment, by reformulating corporate residence in domestic law and tax treaties.
Keywords: Economics Law; International business; International taxation; Multinational enterprises; Resident companies; Tax avoidance; Tax planning; Taxation